Pengaruh Pemberian Insentif Terhadap Motivasi Kerja Pustakawan di Perpustakaan Universitas Bung Hatta Padang - Sumbangsih, Nining; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of this research is: (1) describe the system of incentives provided by the University Library to the Bung Hatta The librarian; (2) describe the motivation system of awarding work to Bung Hatta University in Padang librarian; (3) describe the effects of the granting of incentives to motivate librarians working in the library of University of Bung Hatta desert. Data were collected through observation and interviews with librarians in University Bung Hatta desert. Descriptive data analysing school financing is carried out. Keywords: incentives; motivation